029 Does a heavy baby become a strong child? Grip strength at 4 years in relation to birthweight. (16th November 2010) - Dodds, R; Macdonald-Wallis, C; Kapasi, T; Aihie-Sayer, A; Robinson, S; Godfrey, K; Cooper, C; Harvey, N; Inskip, H; ,
Abstract : Objective: Consistent positive relationships have been found between birthweight and grip strength in young, middle-aged and older adults, suggesting that early influences on the growth and development of muscle are important for muscle function later in the lifecourse. However there are limited data in children. We aimed to assess the relationship between birthweight and grip strength in children aged 4 years. Design: Prospective general population birth cohort study with data from birth to four years, drawn from the Southampton Women's Survey. Grip strength was measured using a Jamar handgrip dynamometer at age four years. We also measured height and weight and assessed body composition (lean mass) using dual energy x-ray absorptiometry. Multiple regression was used to relate grip strength to birthweight allowing for adjustment for confounding factors. Setting: Southampton, UK. Participants: 968 children took part in a sub-study assessing body composition and had their grip strength measured at age four years. Their socio-demographic characteristics were similar to the remainder of the cohort. Main outcome measure: Grip strength in kilograms. Results: Birthweight was positively associated with grip strength, with each kilogram of birthweight being associated with a 0.5 kg increase in grip strength (95% CI 0.30 to 0.70). Grip strength was also strongly related to current body size and adjustment of the birthweight relationship for height and weight attenuated the relationship such that it became non-significant with a 1kg increase in birthweight being associated with 0.15kg (95% CI -0.05 to 0.34kg) increase in grip strength. Adjustment for absolute and percentage lean mass instead of height and weight attenuated the relationship still further such that only a 0.07kg (95% CI −0.16 to 0.30) increase in grip strength was seen in relation to a 1kg increase in birthweight. Conclusion: Birthweight is associated with muscle strength in children aged 4 years. Adjustment for current body size or lean mass explains the relationship suggesting that muscle size is on the causal pathway. Early influences on muscle growth and development appear to impact on grip strength in children as well as adults.